Wildlife associated with burrows of dolichotis patagonum in Central West Argentina - Gatica, Ailin (2020)
Community structure is strongly influenced by positive interactions between species. Detecting and describing these interactions is essential in the study of communities. Dolichotis patagonum Zimmer-mann, 1780 (CN: mara) is a cavid rodent that builds burrows for breeding. In this study, camera traps were used to identify which species use the burrows built by maras in Sierra de las Quijadas National Park, San Luis, Argentina. All burrows were used by other species. A total of 68.7% of all medium-and small-sized taxa recorded in this study used the burrows. This is a clear indicator of the role of D. patagonum as an ecosystem engineer in this environment.